What drives effective competition in the airline industry? An empirical model of city-pair market concentration. (April 2018) - Oliveira, Marcus V.R.; Oliveira, Alessandro V.M.
Abstract: Market concentration is a widely recognized metric for assessing effective competition, as it provides a quantification of the relative success of large, mid-sized and smaller firms in the battle for consumers. Concentration has been a public policy issue in the airline industry since deregulation, due to the long-standing airport dominance by major carriers, which is a concern that is recurrently intensified by merger announcements. This paper develops an empirical model to examine the evolution of concentration in the airline markets. We analyze the case of the Brazilian airline industry, in which the two major carriers acquired a combined market share of more than 90% in the late 2000s and have experienced a sharp reversion since then. We test hypotheses regarding the association of market concentration with market size and service quality, as well as the impacts of vertical relationships after airport privatization. Our results suggest that the entry-attraction effect of market size more than compensates for the economies-of-density effect, while the vertical product differentiation created by the strategic investment in capacity is a key driver of concentration in the airline industry. Highlights: We develop an empirical model to examine the evolution of concentration in the airline markets. We test the association of market concentration with market size and service quality. We also test the impacts of vertical relationships after airport privatization. Our results suggest that the entry-attraction effect of market size more than compensates the economies-of-density effect. Vertical product differentiation created by strategic investment in capacity seems to be a key driver of concentration.